LEMBAGA KEUANGAN MIKRO DARI ASPEK YURIDIS (Suatu Penelitian di Kota Banda Aceh) - AHMAD YANI (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2018)
Most residents of Banda Aceh City do not have the oppurtunity to get financing from banking institutions, because they do not have the legality of business and collateral. Financial institutions are one of the alternatives offered by the law on Microfinance Institutions, currently in Banda Aceh incorporated in the form of Baitul Qiradh cooperative law. In addition Banda Aceh City Goverment also intitiated this Micro Finance Intitutions, which is the only Micro Finance Intitution in Indonesia owned by local government.Keywords: Financial Intitutions, Micro Enterprise and Legal Entity